Outcrops of West Crocker Formation - A Field Visit - Mohammad Syaiful (Ikatan Ahli Geologi Indonesia, 2001)
West Crocker Formation is located in Northwest Sabah of Borneo (Kalimantan) Island. This formation was deposited during Late Palaeogene (Oligocene) and is undoubtedly the best exposed example of a classic submarine fan system in the Asian region.A field visit had been done in August 1999 to view the outcrops of West Crocker Formation. These have been well-exposed in Kota Kinabalu and its vicinity. In fact, the field trip had been held to also visit other Paleogene and younger Neogene rocks in Labuan Island and Brunei areas. In this text, only the outcrops of West Crocker Formation will be discussed.